2021
DOI: 10.3390/separations8100167
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Harvest Time, Method of Preparation and Method of Distillation on the Qualitative Properties of Organically Grown and Wild Helichrysum italicum Immortelle Essential Oil

Abstract: The most important process in immortelle is the extraction of the essential oil by distillation. The chemical properties of the plant depend largely on the cultivation type, climatic conditions and agrotechnical measures. In this work, studies were carried out on organically grown and wild immortelle harvested during the summer (July) and autumn (October) seasons of 2020. Immortelle samples were prepared by drying naturally in two ways: in direct sunlight and in shade. To extract the essential oil, immortelle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…This parameter depends not only on the plant organ (raw material). According to some authors, it is related to the developmental stage of the plant, too [16,41,43]. In the essential oils obtained in our study, 33 compounds were identified, accounting for 94.71% of the total identified fraction in the herb, and 94.75% in the inflorescences.…”
Section: Essential Oil Content and Compositionmentioning
confidence: 49%
See 1 more Smart Citation
“…This parameter depends not only on the plant organ (raw material). According to some authors, it is related to the developmental stage of the plant, too [16,41,43]. In the essential oils obtained in our study, 33 compounds were identified, accounting for 94.71% of the total identified fraction in the herb, and 94.75% in the inflorescences.…”
Section: Essential Oil Content and Compositionmentioning
confidence: 49%
“…In our study, the content of essential oil was higher in the inflorescences (0.31 g × 100 g −1 ) than in the herb (0.25 g × 100 g −1 ) (Table 2). According to the literature data, the content of essential oil in the herb of H. italicum may vary from 0.08 to 0.32%, while in the inflorescences from 0.10 to 0.18% [16,[41][42][43]. This parameter depends not only on the plant organ (raw material).…”
Section: Essential Oil Content and Compositionmentioning
confidence: 99%
“…For this reason, choosing the appropriate plant genetics, climate, and soil, as well as altitude, are important parameters that may significantly influence the EO content and composition [8][9][10]. Further, harvest time and distillation method could also significantly affect the plant's EO content and profile [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos de Ascrizzi et al (14) , Salama e Khater (15) , Matin et al (16) e Oliveira et al (17) apresentam indícios da influência das épocas de colheita na produtividade das espécies da família Asteraceae. Assim, o presente estudo busca contribuir com a produção de jambu na Amazônia, ao indicar os períodos de colheita que podem otimizar a produção de sementes crioulas.…”
unclassified